Protecting asset value and driving performance with a dynamic, risk-based contingency fund - Mauelshagen, Craig William; Pollard, Simon J. T.; Owen, D.; Herndlhofer, S.; Firth, P.; McKenna, J.; Bingley, N.; Jenson, P. (Springer, 2014)
We present a risk-based contingency fund management methodology to mitigate the impact of external risks on asset value and performance. Many asset intensive industries, such as water and energy utilities, are significantly affected by external risks such as extreme weather events. We put the case for a centrally held risk-based contingency fund that would mitigate against ‘medium’ impact ‘medium’ probability events that fall outside of large losses covered by insurance and smaller ‘normal’ operating losses. Our risk-based contingency approach is appropriate for short-term business planning (1–5 years) and would complement longer term planning, for example climate change adaptation and mitigation strategies. Our approach offers a risk-based methodology to manage contingency that is explicit and defensible. Critically, our methodology allows contingency to be managed dynamically as risk probabilities and impacts change, creating a mechanism for contingency funds to be periodically released if risk exposure reduces. The long-term benefit of dynamic, risk-based contingency is to reduce the impact of external risks and support long-term sustainability.
Keywords: Contingency; Risk; Performance; Asset management